G124(P) Paediatric part-task simulation for new starters – goodbye to 'see one, do one, teach one'?. (May 2019) - Mullen, N; Whittle, V
Abstract : Aims: Trainees often have little experience in performing key skills prior to their first attempt on real children. Task training improves clinicians' competence and reduces complications for patients. We wanted to establish if a part-task course could improve new trainees' knowledge, skills and confidence in four essential paediatric competencies: Lumbar puncture Intraosseous access Intravenous cannulation Neonatal intubation Methods: We delivered this one day course prior to the start date for new Level 1 trainees. There were 22 participants. There were three individual workshops each with paediatric specific task training manikins: vascular access (intra-osseous and intra-venous), lumbar puncture, and neonatal intubation. There were a minimum of two facilitators at each station. We assessed pre and post-course knowledge and confidence via a multiple choice examination and Likert scale questionnaire respectively. Every trainee was given the opportunity to attempt each task at the beginning of each station. They then performed the task repeatedly with targeted feedback until they reached a pre-defined level of competence. Results: The vast majority of participants had no prior practical experience of either intubation or intra-osseous access. Just under half had successfully performed a lumbar puncture on a child while all had previously managed to successfully cannulate a child. Post-course confidence increased in each domain with the exception of intravenous cannulation in which the majority of participants were already confident. Overall confidence increased by 22% on the Likert scale (30% when cannulation was removed from the analysis). All trainees met the required standard for each task. MCQ scores increased by an average of 15% on baseline. Participant feedback was strongly positive with 93% 'Strongly agreeing' that they would put their learning into practice. Conclusion: Part task training improves new trainees' confidence of and knowledge in key paediatric procedures. We believe that trainees should have high quality task-based simulation training prior to undertaking them in clinical practice. We anticipate improvement in participants' task success in the work place although greater time and resources are required to assess real world competence and patient level outcomes.